Contingent Faculty as Nonideal Workers. Issue 176 (December 2016) - Kezar, Adrianna; Bernstein‐Sierra, Samantha
Abstract : This chapter explores how contingent faculty address the issue of work and family and demonstrates the importance of understanding the diversity of contingent faculty experiences and of underemployment rather than notions of the ideal worker to explain their work lives.